Expression and Regulatory Network Analysis of miR-140-3p, a New Potential Serum Biomarker for Autism Spectrum Disorder - Cirnigliaro, Matilde; Barbagallo, Cristina; Gulisano, Mariangela; Domini, Carla N.; Barone, Rita; Barbagallo, Davide; Ragusa, Marco; Di Pietro, Cinzia; Rizzo, Renata; Purrello, Michele (Frontiers in Molecular Neuroscience, 2017)
Given its prevalence and social impact, ASD (Autism Spectrum Disorder) is drawing much interest. Molecular basis of ASD is heterogeneous and only partially known. Many factors, including disorders comorbid with ASD, like TS (Tourette Syndrome), complicate ASD behavior-based diagnosis and make it vulnerable to bias. To further investigate ASD etiology and to identify potential biomarkers to support its precise diagnosis, we used TaqMan Low Density Array technology to profile serum miRNAs from ASD, TS, and TS+ASD patients, and unaffected controls (NCs). Through validation assays in 30 ASD, 24 TS, and 25 TS+ASD patients and 25 NCs, we demonstrated that miR-140-3p is upregulated in ASD vs: NC, TS, and TS+ASD (Tukey's test, p-values =0.03, =0.01, <0.0001, respectively). ΔCt values for miR-140-3p and YGTSS (Yale Global Tic Severity Scale) scores are positively correlated (Spearman r =0.33; Benjamini-Hochberg p-value =0.008) and show a linear relationship (p-value =0.002). Network functional analysis showed that nodes controlled by miR-140-3p, especially CD38 and NRIP1 which are its validated targets, are involved in processes convergingly dysregulated in ASD, such as synaptic plasticity, immune response, and chromatin binding. Biomarker analysis proved that serum miR-140-3p can discriminate among: (1) ASD and NC (Area under the ROC curve, AUC: 0.70; sensitivity: 63.33%; specificity: 68%); (2) ASD and TS (AUC: 0.72; sensitivity: 66.66%; specificity: 70.83%); (3) ASD and TS+ASD (AUC: 0.78; sensitivity: 73.33%; specificity: 76%). Characterization of miR-140-3p network would contribute to further clarify ASD etiology. Serum miR-140-3p could represent a potential non-invasive biomarker for ASD, easy to test through liquid biopsy.